2014
DOI: 10.1097/qai.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Health Communication in the Continuum of HIV Care, Treatment, and Prevention

Abstract: Health communication has played a pivotal role in HIV prevention efforts since the beginning of the epidemic. The recent paradigm of combination prevention, which integrates behavioral, biomedical, and structural interventions, offers new opportunities for employing health communication approaches across the entire continuum of care. We describe key areas where health communication can significantly enhance HIV treatment, care, and prevention, presenting evidence from interventions that include health communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…Finally, information needs assessments are only relevant if healthcare providers and organizations use the data obtained to improve patient care. But when these changes are made, studies have shown that meeting patient health-information needs can lead to better outcomes (Flickinger, Saha, Moore, & Beach, 2013; Tomori et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, information needs assessments are only relevant if healthcare providers and organizations use the data obtained to improve patient care. But when these changes are made, studies have shown that meeting patient health-information needs can lead to better outcomes (Flickinger, Saha, Moore, & Beach, 2013; Tomori et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…16,73,75,76,8790 Before support can be received though, disclosure must occur and disclosure has been found to be a major barrier to ART initiation. 77,82,85,91,92 Disclosure to friends and family enables patients to access the psychosocial and material support crucial for initiating and staying on treatment.…”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%
“…Barriers at the community level include stigma and discrimination, 16,7476,81,89,9497 limited ART knowledge within the community, lack of community involvement in program planning, and lack of community mobilization around ART. 74,78,94,96 Inequitable gender norms, including community stereotypes of masculinity and femininity are key determinants of delayed linkage to care and treatment.…”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations